The relationship between macroalgal morphological complexity and hydraulic conditions in stream habitats - Tonetto, Aurélio Fajar [UNESP]; Cardoso-Leite, Ricardo; Novaes, Marcos Carneiro; Guillermo-Ferreira, Rhainer (Springer, 2015)
The effects of habitat complexity have been considered important factors for the evolution of morphological complexity in organisms. We assessed the possible relationship between hydraulic niche conditions and the morphological complexity of algal filaments by sampling four species of macroalgae inhabiting different hydraulic niches in two freshwater streams. These algal species exhibit different fractal dimensions, which were measured by applying a grid method. The results showed that morphological differences are a function of hydraulic niche for stream macroalgae. Algae with complex shape (Nitella wrightii and Batrachosperum puiggarianum) were established in slower flows, while algae with simpler filament shape (Vaucheria sp. and Oedogonium sp.) were more likely to occur in faster water currents. The sites where the species occurred are a reflection of their ability to hold position, which is ultimately driven by their morphology. The influence of flow in stream habitats is an important factor for lotic macroalgae settlement and its effects can be related to evolutionary adjustment of body shape in these environments. We suggest that the morphological structure (here as fractal dimension) of freshwater macroalgae can be considered an adaptation to the costs and benefits exhibited by different hydraulic niches.
Keywords: Morphological complexity; Stream macroalgae; Water flow; Fractal dimension